Timing, Biometry, Selection of Intraocular Lens, Complications and Other Problems in Traumatic Cataracts - Mümin Hakan Eren (Türk Oftalmoloji Dergisi, 2012)
Traumatic cataract is a frequent consequence of trauma to the eye. Management of traumatic cataract and timing of surgery are based on location and morphology of the lens opacity, visual acuity, intraocular pressure control, presence of intraocular inflammation, and ability to examine the posterior segment. Modern advances in microsurgical techniques have enhanced the results of cataract surgery. Primary intraocular lens implantation has achieved good visual results in an increasingly large number of patients. Careful examination and accurate diagnosis are critical in surgical decision-making, both in the choice of the most appropriate timing for surgery and the selection of the best surgical technique. (Turk J Ophthalmol 2012; 42: Supplement 31-5)